Perception of oil palm estate managers towards oil palm-cattle integration - Assis, K; Mohd Hafify, A; Mohammad Amizi Ayob; Zulhisyam Abdul Kari @ Abdullah; Mohd Sukhairi MatRasat; Mazlan Mohamed (2014)
The oil palm industry is a major contributor in the export of Malaysian agriculture. The National Agriculture Policy (1992 – 2010) included beef production through integration as an important strategy to increase national beef output and to achieve the self-sufficiency level. Therefore,the main objective of this study was to investigate the perception of oil palm estate managers towards the integration between oil palm and cattle and towards factors which causing the slow implementation of the integration in Malaysia.A survey method through self-completion questionnaire was used in collecting the required data from the managers which consist of managers, assistant managers, supervisors and also owners of the selected oil palm estates in Kelantan, Malaysia. A total of 60 respondents were selected by using simple random sampling method and 15 of them were managing the oil palm estate which implementing the oil palm-cattle integration. The data gathered was analyzed by using descriptive and inferential statistics. Factor analysis revealed that there were two main components of perception of the respondents on the oil palm-cattle integration. And factor analysis also identified that there were two main factors that causing the slow implementation of the oil palm-cattle integration based on the respondents’ perception which are internal factor and external factor. An independent samples t-test showed that there was a significant different in the perception on the internal factor between the respondents who managing the estate which implementing the oil palm-cattle integration and the respondents who managing the estate which not implementing the integration. The study concludes that the government needs to plan a good strategy in promoting the oil palm-cattle integration by taking into account all the internal as well as external factors which could cause the slow implementation of the oil palm-cattle integration in Malaysia